The Benefits of Indolence. - Bugayenko, Yegor (Communications of the ACM, 2019)
The author discusses the issue of software developers going above and beyond to fix problems. He mentions the policy of his software company Zerocracy to refrain from being altruistic and the problems of dealing with legacy code and lack of software libraries. The article presents comments from other programmers regarding the topics he discusses.